Analisis Penggunaan Platform Digital Youtube Terhadap Perkembangan Bahasa Anak Usia Dini 4 - 6 Tahun - Elok Faiqotul Hikmah; Fenti Nur; Ansori (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
The development of digital technology has made YouTube one of the most widely accessed platforms by young children. This platform's presence has a diverse impact on children's language development, depending on usage patterns. Based on observations, interviews, and documentation, it was found that YouTube use can provide positive language stimulation when supported by controlled usage duration, age-appropriate content selection, and active parental guidance. Children who frequently access educational content such as children's songs, stories, letter recognition, numbers, and colors, and interactive learning show improvements in vocabulary, listening skills, language comprehension, and communication skills. Conversely, excessive, unsupervised YouTube use tends to reduce the intensity of children's verbal interactions with their surroundings and potentially hinders social language development. The results also indicate that content quality plays a more dominant role than quantity of use. Furthermore, parental involvement in explaining video content, engaging children in discussions, and connecting content to everyday experiences can transform viewing into a more interactive and meaningful learning process. These findings confirm that YouTube can function as an effective language stimulation medium for young children when used proportionally, with active guidance, and directed toward educational content.